First principles kinetic Monte Carlo study on the growth patterns of WSe2 monolayer. (20th May 2016) - Nie, Yifan; Liang, Chaoping; Zhang, Kehao; Zhao, Rui; Eichfeld, Sarah M; Cha, Pil-Ryung; Colombo, Luigi; Robinson, Joshua A; Wallace, Robert M; Cho, Kyeongjae
Abstract: The control of domain morphology and defect level of synthesized transition metal dichalcogenides (TMDs) is of crucial importance for their device applications. However, current TMDs synthesis by chemical vapor deposition and molecular beam epitaxy is in an early stage of development, where much of the understanding of the process-property relationships is highly empirical. In this work, we use a kinetic Monte Carlo coupled with first principles calculations to study one specific case of the deposition of monolayer WSe2 on graphene, which can be expanded to the entire TMD family. Monolayer WSe2 domains are investigated as a function of incident flux, temperature and precursor ratio. The quality of the grown WSe2 domains is analyzed by the stoichiometry and defect density. A phase diagram of domain morphology is developed in the space of flux and the precursor stoichiometry, in which the triangular compact, fractal and dendritic domains are identified. The phase diagram has inspired a new synthesis strategy for large TMD domains with improved quality.